Evaluating the Qualitative Effectiveness of a Novel Pollinator: a Case Study of Two Endemic Hawaiian Plants. (November 2014) - Aslan, Austin; Hart, Patrick; Wu, Joanna; Aslan, Clare E.
Abstract In situations where native mutualists have become extinct, non‐native species may partner with remnant native species. However, non‐native mutualists may differ behaviorally from extinct native mutualists. In the case of pollination, novel relationships between natives and non‐natives could differ both quantitatively and qualitatively from native–native relationships. In Hawai'i, the non‐native Japanese White‐eye (Zosterops japonicus) has largely replaced endemic birds as pollinator of the endemic Clermontia parviflora and C. montis‐loa. We surveyed Clermontia patches and found that they ranged from 106 to 1198 m in diameter. We performed manual pollination of flowers with pollen taken from plants at five distance categories, ranging from 0 (self‐fertilization) to 20 km, and examined the germination of resulting seeds. We used radiotelemetry to estimate daily Japanese White‐eye movement distances. Percent germination of seeds after short‐ to intermediate‐distance pollination crosses (i.e., 20–1200 m, or intra‐patch pollen transfer distances) significantly exceeded germination of seeds from selfed trials for C. parviflora. No significant differences in germination rates among treatments were detected for C. montis‐loa. The maximum daily movement distances of radio‐tracked birds were generally <1 km. Together, these results suggest that this novel pollinator may be an effective mutualist for both Clermontia species. This study serves as an example of research examining qualitative components of novel mutualism, which are generally neglected relative to quantitative components.